Fourth Five Year Plan A Preliminary Memorandum Government of Uttar Pradesh - Planning Commission (Planning Commission, 1968)
The Himalayan region is mountainous having extensive and thick forests. It comprises Uttar Kashi, Chamoli, Pithoragarh, Tehri Garhwal, Garhwal and Ahnora districts, Naini Tal tahsil of Naini Tal District and Chakrata and a part of Dehra Dun tahsil of Dehra Dun district. This region is thinly populated and there are no large towns, though there are a number of beautiful hill stations like Chakrata, Mussoorie, Naini Tal, Ranikhet and Ahnora. Dehra Dun is the only city with a population of more than one lakh. On account of the stony nature of the land cultivation is possible only in river valleys and terraced hill slopes.
Planning Department